2007
DOI: 10.1159/000110008
|View full text |Cite
|
Sign up to set email alerts
|

Sonodynamic Antitumor Effect of Protoporphyrin IX Disodium Salt on S180 Solid Tumor

Abstract: Background: The sonodynamically induced antitumor effect of protoporphyrin IX (PPIX) disodium salt was studied in mice bearing sarcoma 180 solid tumors. Methods: In order to determine the optimum timing of ultrasound exposure after administration of PPIX, the PPIX concentrations in plasma, skin, muscle and tumor were estimated by measuring the fluorescence intensity of tissue extractions with a fluorescence photometer based on the standard curve. Antitumor effects were estimated by measuring tumor size and cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 49 publications
2
23
0
Order By: Relevance
“…In contrast, a long DUI allows diffusion of the sonosensitizer into the tissue, to be accumulated in the tumor cellular compartment, so that the subsequent sonication will generate more direct tumor cytotoxicity (i.e., cellular-targeting sonosensitization). SDT is usually thought to maximize its therapeutic effect on tumors and minimize side effects on the surrounding healthy tissues when the sonosensitizer ratio of tumor to normal tissue is maximal [8,11]. However, in recent years, increasing evidence in photodynamic therapy (PDT) accumulated suggests that plasma concentration (which reflects endothelial cell exposure) correlated better with the therapeutic effect than tumor concentration [38][39][40][41][42].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, a long DUI allows diffusion of the sonosensitizer into the tissue, to be accumulated in the tumor cellular compartment, so that the subsequent sonication will generate more direct tumor cytotoxicity (i.e., cellular-targeting sonosensitization). SDT is usually thought to maximize its therapeutic effect on tumors and minimize side effects on the surrounding healthy tissues when the sonosensitizer ratio of tumor to normal tissue is maximal [8,11]. However, in recent years, increasing evidence in photodynamic therapy (PDT) accumulated suggests that plasma concentration (which reflects endothelial cell exposure) correlated better with the therapeutic effect than tumor concentration [38][39][40][41][42].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the energy of the ultrasound wave can be focused on sites of malignancy and, thus, locally activate sonosensitizers that have preferentially accumulated in tumor tissues, causing injuries to desired cells with minimal damage to peripheral healthy tissue. Currently, studies of SDT have mainly focused on its direct killing effects on tumor cells [8][9][10][11][12]. Many mechanisms had been proposed by different research groups, including apoptosis [13][14][15][16][17] and autophagy [18,19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These morphological cell changes occurring immediately after exposure may be due to an ultrasonic mechanical effect. The plasma membrane is a dynamic and complex structure which connects the cell with the environment and coordinates most intercellular communication; changes on the surface of the cell membrane will subsequently affect membrane functions and eventually lead to cell lysis, apopto- sis and necrosis [19][20][21] . In addition, membrane LPO and hydroxyl radicals were generated in the culture medium immediately after treatment, and results showed that the LPO levels and hydroxyl radicals in the cell suspensions were obviously increased after 30 s of ultrasound exposure (p !…”
Section: Discussionmentioning
confidence: 99%
“…The therapy's effectiveness has also been demonstrated in more deeply located tumors including those of the central nervous system (Ohmura et al 2011; Gao et al 2013; Jeong et al 2012). Post-therapy histologic studies have consistently shown damage to the ultrastructure of the cancer cells including destruction of cell membranes, mitochondrial swelling and chromatin condensation (Liu et al 2006[b], 2007[a, b], 2008; Wang et al 2008[a], 2011[c], 2012[b]); it was considered that these changes induced by the therapy may have mediated cancer cell death. Combining photodynamic therapy with sonodynamic therapy had a synergistic effect in solid tumors with additional post-therapy tumor necrosis, inhibition of tumor growth and increased survival times (Jin et al 2000; Tserkovsky et al 2012).…”
Section: Sonodynamic Therapymentioning
confidence: 99%